2020
DOI: 10.5194/amt-13-1517-2020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of functional groups in atmospheric aerosols by infrared spectroscopy: method development for probabilistic modeling of organic carbon and organic matter concentrations

Abstract: Abstract. The Fourier transform infrared (FTIR) spectra of fine particulate matter (PM2.5) contain many important absorption bands relevant for characterizing organic matter (OM) and obtaining organic matter to organic carbon (OM∕OC) ratios. However, extracting this information quantitatively – accounting for overlapping absorption bands and relating absorption to molar abundance – and furthermore relating abundances of functional groups to that of carbon atoms poses several challenges. In this work, we define… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 103 publications
(146 reference statements)
1
21
0
Order By: Relevance
“…The average OM:OC estimates for samples influenced by wildfires and residential wood burning were reported to be 1.65 and 1.45, respectively (Bürki et al, 2020) compared to 1.65 and 2 (AMS and MIR spectroscopy obtained close values) for primary and aged WB aerosols in this work. The average OM:OC estimates for these atmospheric burning-influenced samples 450 are clearly closer to that of primary WB aerosols in chamber.…”
Section: Om:oc Ratiosmentioning
confidence: 47%
See 4 more Smart Citations
“…The average OM:OC estimates for samples influenced by wildfires and residential wood burning were reported to be 1.65 and 1.45, respectively (Bürki et al, 2020) compared to 1.65 and 2 (AMS and MIR spectroscopy obtained close values) for primary and aged WB aerosols in this work. The average OM:OC estimates for these atmospheric burning-influenced samples 450 are clearly closer to that of primary WB aerosols in chamber.…”
Section: Om:oc Ratiosmentioning
confidence: 47%
“…While each FG is not a marker for any specific source, their proportions could possibly be informative when used with multivariate methods. Cluster analysis by Bürki et al (2020), for example, identified 45 burning-influenced samples (in 3050 samples) based on their spectral similarity (i.e. FG proportions and organic-to-inorganic ratio), which were supported, to some extent, by matching their collection time and location with the known burning events (e.g.…”
Section: Identification Of Burning-influenced Samplesmentioning
confidence: 97%
See 3 more Smart Citations